Assessing Regional Integration in Africa - Nations Unies (United Nations, 2006)
This report provides a comprehensive evaluation of the state of Africa’s integration process, showing where efforts have succeeded or failed including why intra African trade remains low; and how lack of macro-economic policy convergence and insufficient infrastructures hamper integration.